Peningkatan Pertumbuhan Tebu dengan Aplikasi Kompos, Cendawan Mikoriza Arbuskular dan Pembenah Tanah di Lahan Kering Madura - Arinta Rury Puspitasari; Diana Ariyani; Sri Winarsih (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Puspitasari AR, Ariyani D, Winarsih S. 2021. Increasing the growth of sugarcane with compost, mycorrhizae and soil moisturizer applications in dry land Madura. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 392-399. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the problems in sub-optimal land at Madura is limited water which results in low sugarcane productivity. Therefore, it is necessary to maintain soil moisture through the application of mycorrhizae and soil moisturizer. The aim of the study was to obtain a technology package for sugarcane cultivation on sub-optimal land in the Madura region, especially Bangkalan Regency. The experiment was carried out in Bangkalan, Madura on an irrigated dry land area from March to November 2015. The variety used was Bululawang. Soil moisturizer, namely acrylamide polymer in the form of dry granule with the size of L. Mycorrhizal fungus used was Glomus sp. The study was designed on a split plot design. The main plot was the application of organic matter compost 10 tonnes/ha and without the application of compost. Subplots consisted of 4 treatments, mycorrhizae 5 grams per 2 eyes budsett, soil moisturizer 20 kg/ha, a combination of mycorrhizae and soil moisturizer and without mycorrhizae and soil moisturizer (control). Each treatment was repeated three times. The results of the observations were analyzed using Analysis of Variance and continued with Least Significant Difference Test 5% (LSD 5%). The results of the experiment showed that the use of compost, mycorrhizae and soil moisturizer increased the number of tillers and stalks of sugarcane. The combination of compost, mycorrhizae and soil moisturizer could enhance number of tillers 36.99% and number of stalks 42.16% significantly different to control.